The Influence of Situasional Leadership, Organizational Culture and Training on Employee Performance and Work Motivation of Millenial Generation at the Inspection Office of BRI Malang - Mohammad Reza; Rofiaty Rofiaty; Atim Djazuli (Wacana Journal of Social and Humanity Studies, 2018)
Generation Millenial or Gen Y is the labor force that will dominate in every company in the next few years in Indonesia, as well as in banking such as Bank Rakyat Indonesia and Inspection Office of BRI Malang in particular. The purpose of this research is to know the influence of situational leadership, organizational culture and training on employee performance and work motivation of millenial auditors at Inspection Office of BRI Malang. This study used a sample of 63 millenial auditors with partial least square method (PLS). The results of this study indicate, situational leadership has significant influence on employee performance and work motivation of millennial auditor at the Inspection Office of BRI Malang. However, organizational culture has insignificant influence on employee performance and work motivation and also has insignificant influence on employee performance through work motivation. Training has insignificant influence on employee performance but has significant influence on work motivation and also on employee performance through work motivation. Work motivation has significant influence on employee performance. The findings in this study indicate that a rigid organizational culture and training that does not improve skills and provide a space of appreciation to the millennial auditor, have insignificant influence on employee performance and work motivation at the Inspection Office of BRI Malang.